High‐density lipoprotein cholesterol levels are associated with major adverse cardiovascular events in male but not female patients with hypertension. Issue 5 (30th March 2021) - Wang, Xiaopu; Pei, Junyu; Zheng, Keyang; Hu, Xinqun
Abstract: Background: The relationship between high‐density lipoprotein cholesterol (HDL‐C) levels and major adverse cardiovascular events (MACEs) in hypertensive patients of different sexes is unclear. Hypothesis: Sex differences in the relationship between HDL‐C levels and the risk of MACEs among hypertensive patients. Methods: We performed a post‐hoc analysis of data obtained from the Systolic Blood Pressure Intervention Trial (SPRINT) and explored sex‐based differences in the relationship between HDL‐C levels and MACEs among hypertensive patients using Cox proportional hazards regression. Results: A total of 9323 hypertensive patients (6016 [64.53%] men and 3307 [35.47%] women) were assessed using SPRINT data. MACEs occurred in 395 (6.57%) men and 166 (5.02%) women after a mean follow‐up of 3.26 years. When HDL‐C levels were used as a continuous covariate, each 10 mg/dl increase in HDL‐C levels decreased the risk of MACEs in men (hazard ratio [HR], 0.78; 95% confidence interval [CI], 0.70–0.88; p  < .0001). However, HDL‐C levels were not associated with MACEs in female hypertensive patients (HR, 1.02; 95% CI, 0.89–1.16; p  = .7869). Compared with those in the first quartile, MACEs in the fourth quartile had the lowest risk among male patients (HR, 0.58; 95% CI, 0.41–0.82; p  = .0023). Female patients in the fourth quartile of HDL‐C levels had an HR of 1.09 for MACEs (95% CI, 0.62–1.93; p  = .7678). HDL‐C levels were not associated with the risk of MACEs among females. Conclusion: Among elderly hypertensive patients, higher HDL‐C levels were associated with a lower MACE incidence in men but not in women. Unique identifier: NCT01206062.